Динаміка становлення соціальної політики ЄС: основні етапи - Івасечко, Ольга (Видавництво Львівської політехніки, 2014)
Розглянуто основні етапи еволюції соціальної політики ЄС та ключові досягнення на цих етапах. З’ясовано трактування соціального виміру в межах інтеграційного об’єднання, що передбачає створення універсальної системи соціального забезпечення, дотримання єдиних соціальних стандартів, фундаментальною основою яких є уніфіковане соціальне законодавство. The work observes the main stages of the evolution of the social policy of European Union and key achievements at these stages. It clarifies the interpretation of the social dimension within the association which envisages the creation of a universal social security system, the compliance of the common social standards with the fundamental basis of a unified social legislation. The author describes transformation of structures associated with the social dimension, analyzes the features of distinguishing the EU social policy in the direction of an independent and permanent expansion of competence in this area. The work highlights the integrated vision of social policy that is consolidated in the official declarations and practices of the states and subjects of international relations directed towards the protection and improving the quality of living standards in the member states of the EU. Also, it determines the interstate aspect of social policy that envisages economic, environmental, educational, and ethical activity of geopolitical subjects that is aimed towards changing of the trends or maintaining the status quo in the social environment in the context of international relations development. The article defines a complex mechanism of the implementation of the social policy of the Community that has been forming during several decades. Special attention is paid to separate components of the social policy of the Association such as the following: ensuring the rights of migrant workers, ensuring healthy and safe working conditions, etc. The social values such as equality and non-discrimination have been actively implemented. The current stage of the EU social policy is associated with the construction of a social Europe which foresees gradual creation of a socially homogeneous space across the EU.
The dynamics of formation of the EU social policy: the main stages
Keywords: соціальна політика ЄС; соціальний вимір; соціальний простір; принципи соціальної політики; EU social policy; social dimension; social space; the principles of social policy